TRANSFORMASI DIGITAL DAN FINANCIAL TECHNOLOGY TERHADAP PENINGKATAN PENDAPATAN UMKM DIMASA PANDEMI COVID-19 DI KABUPATEN PASURUAN: Transformasi Digital, Financial Technology, Peningkatan Pendapatan UMKM - Asadi, Asadi; Sularsih, Hermi (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This research aims to determine the effect of Digital Transformation and Financial Technology on Increasing MSME Income during the Covid-19 Pandemic in Pasuruan Regency. This type of research is a type of quantitative research with a set sample of 400 respondents. Multiple regression analysis test using SPSS. The results of the study show that the Digital Transformation and Financial Technology variables significantly have a positive effect on increasing MSME income during the Covid-19 pandemic.